Cognitive Constraints Shape Public Debate on the Risks of Synthetic Biology. Issue 12 (December 2018) - Swiney, Lauren; Bates, Declan G.; Coley, John D.
Abstract : We consider efforts to understand public perceptions of synthetic biology, describing a novel cognitive science approach indicating that cognitive biases constrain risk perceptions of synthetic biology. We discuss the implications of these findings and outline how they may be harnessed to improve the quality of public debate.